Comparison of dietary macro and micronutrient intake with physical activity levels among children with and without autism: a case-control study - Moludi, Jalal; Ebrahimi, Behzad; Maleki, Vahid; Saiedi, Somaiyeh; Tandoroost, Arash; Jafari-Vayghyan, Hamed; Alizadeh, Shahab; Djafarian, Kurosh (Progress in Nutrition, 2020)
Background: Physical activity is an important part of healthy lifestyle especially for autistic children. A few studies have previously compared the differences of diet intake and physical activity patterns in autistic and healthy children. This study was aimed to compare the macro-and micronutrient intake and physical activity patterns between children with and without autism. Materials and Methods: The present case-control study was conducted on 59 boys aged 6 to 13 years with autism and healthy children. Dietary intake of subjects was measured by Food Frequency Questionnaire (FFQ). The physical activity level was recorded for seven days using an ActiGraph accelerometer which categorized by the time of each participant spent, in sedentary, moderate and vigorous activity. Results: The findings revealed that there were significant differences in intake of many dietary factors including energy (p